REVENIND LA PROBLEMA PREDĂRII AFRICATELOR ENGLEZE STUDENŢILOR VORBITORI DE LIMBA ROMÂNĂ - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2007)
This article is a continuation of a series of materials presented and published as conference proceedings. It is dedicated to the issue of teaching English affricates in the context of teaching phonetics to Romanian-speaking students. In this work, there is made an attempt to classify and statistically work typical mistakes committed by Romanian-speaking students when acquiring pronunciation of English affricates, to determine their linguistic motivation, to establish their place in the context of all pronunciation-related mistakes and overall number of mistakes. There are also suggested some indications concerning teaching English affricates to Romanian-speaking students, as well as a set of exercises based on these indications.